The Influence of Classroom Management and Work Ethics on Improving the Quality of Learning - Yusdianti, Novita; Fitria, Happy; Effendi, Darwin (Journal of Social Work and Science Education, 2024)
This research aims to analyze the influence of classroom management and teacher work ethic on the quality of learning in SMP Negeri in Simpangkatis District. Specifically, this research aims to determine: (1) analyze the influence of classroom management on the quality of learning (2) analyze the influence of work ethic on the quality of learning (3) analyze the influence of classroom management and work ethic together on the quality of learning. To obtain accurate research results, in this thesis, the author uses a quantitative approach. The research subjects were several teachers at SMP Negeri in Simpangkatis District. The data collection technique used is a questionnaire technique with a data instrument in the form of a scale, the prerequisite stages of analysis include a normality test, homogeneity, linearity test, multicollinearity test, autocorrelation test, and data heteroscondensity test. Test the research hypothesis using multiple regression. Data collection techniques were carried out through questionnaires distributed to teachers. After conducting research and analyzing the collected data, the following results were obtained: (1) Class management has a positive and significant effect on the quality of learning based on the count value being greater than the table, namely 13.431, greater than table 1.999, (2) Work ethic has a positive effect and significant to the quality of learning based on the calculation results t-count is greater than t-table or 21,453 greater than 1.999, (3) Class management and work ethic have a positive and significant effect together on the quality of learning according to the calculation f-count greater than f-table or 263,400 greater of 3.21.